Synthesis and structural characterization of novel porous zinc substituted nanohydroxyapatite powders. (2nd January 2017) - Garbo, Corina; Sindilaru, Maria; Carlea, Alexandra; Tomoaia, Gheorghe; Almasan, Valer; Petean, Ioan; Mocanu, Aurora; Horovitz, Ossi; Tomoaia-Cotisel, Maria
ABSTRACT: This study reports the synthesis of new porous nanohydroxyapatites (HAPs) substituted with different Zn contents (HAP_Zn) employing calcium and zinc nitrates and diammonium hydrogen phosphate as precursors. The synthesis was conducted in the presence of a surfactant, L-asparagine, for controlling the pore size distribution and morphology of obtained nanopowders, using a co-precipitation route. Thus a new approach leading to HAP_Zn nanopowders with improved nucleation and crystallization ability was developed. After maturation treatment of dispersions and filtration, the precipitate was lyophilized and ground. Part of the samples was calcined at 300°C for 1 h. The zinc content in the nanoHAPs varies from 0.2 to 10 wt% (substitution degree of Ca by Zn from 0.3 to 15.8 mole %). XRD investigations indicated HAP as the unique phase present and the nanostructured nature of the obtained HAPs. FTIR spectra also confirmed the presence of HAP structure. TEM, SEM, and AFM images showed the morphology of the HAP_Zn samples. BET analysis led to the characterization of specific surface area and porosity for the samples. The new nanopowders are designed to be used in orthopedic surgery, particularly for the treatment of osteoporosis and as bone substitutes, and in dentistry for remineralization of enamel.